2020
DOI: 10.1007/s00508-020-01616-x
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of individual therapeutic exercises via smartphone app for patients suffering from non-specific back pain

Abstract: Background The purpose of this qualitative study was the assessment of the feasibility and acceptance of orthopedists prescribing individualized therapeutic exercises via a smartphone app to patients suffering from non-specific back pain. Methods A total of 27 patients (mean age 44.8 ± 13.2 years) diagnosed with acute non-specific back pain were prescribed individually chosen therapy exercises via a smartphone app. Before the patients started and after 4 weeks of exercising all participants went through an ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
(31 reference statements)
1
21
1
Order By: Relevance
“…Furthermore, it is important to mention that wearable devices and smartphone applications offer great potential to tailor, prescribe, and monitor PI [ 76 , 77 ] although a stricter scientific evaluation is often needed with regard to commercially available devices/applications [ 78 , 79 , 80 ]. Notably, it has been shown that smartphone apps can positively influence exercise adherence (e.g., by providing feedback and motivation) [ 81 , 82 , 83 ], which is an important factor determining the effectiveness of a PI.…”
Section: Different Approaches To Prescribing Physical Interventionmentioning
confidence: 99%
“…Furthermore, it is important to mention that wearable devices and smartphone applications offer great potential to tailor, prescribe, and monitor PI [ 76 , 77 ] although a stricter scientific evaluation is often needed with regard to commercially available devices/applications [ 78 , 79 , 80 ]. Notably, it has been shown that smartphone apps can positively influence exercise adherence (e.g., by providing feedback and motivation) [ 81 , 82 , 83 ], which is an important factor determining the effectiveness of a PI.…”
Section: Different Approaches To Prescribing Physical Interventionmentioning
confidence: 99%
“…In this issue, Hasenöhrl et al describe a smartphone app with individualized therapeutic exercises for patients suffering from so-called non-specific (not dangerous) back pain. The authors were able to show that the prescription of therapeutic exercises via smartphone app to patients suffering from non-specific back pain seems to be feasible and well accepted, and their pilot data additionally K Health-enhancing physical activity, exercise and sports-a never-ending success story 113 editorial pointed towards efficacy of this quite new and special intervention [3]. This could be a step into the future-additional to inpatient and outpatient rehabilitation of these patients.…”
mentioning
confidence: 96%
“…Today, the importance of physical activity, exercise and sports concerning health issues cannot be overestimated [1]. For the last decades, exercise in medicine, namely prevention, therapy and rehabilitation seem to have the touch of a never-ending success story [1][2][3]. It is a pleasure for me to highlight two current Viennese approaches concerning this relevant preventive, therapeutic and rehabilitative means within this issue [2,3].…”
mentioning
confidence: 99%
See 2 more Smart Citations